Public Capital in Resource Rich Economies: Is there a Curse? - Bhattacharyya, S; Collier, P (CSAE (University of Oxford), 2011)
As poor countries deplete their natural resources, for increased consumption to be sustainable some of the revenues should be invested in other public assets. Further, since such countries typically have acute shortages of public capital, the finance from resource depletion is an opportunity for needed public investment. Using a new global panel dataset on public capital and resource rents covering the period 1970 to 2005 we find that, contrary to these expectations, resource rents significantly and substantially reduce the public capital stock. This is more direct evidence for a policy-based ‘resource curse’ than the conventional, indirect evidence from the relationships between resource endowments, growth and income. The adverse effect on public capital is mitigated by good economic and political institutions and worsened by GDP volatility and ethnic fractionalization. Rents from depleting resources have more adverse effects than those that are sustainable. Our main results are robust to a variety of controls, and to instrumental variable estimation using commodity price and rainfall as instruments, Arellano-Bond GMM estimation, as well as across different samples and data frequencies.